HOW DO SUSTAINABILITY ASSURANCE, INTERNAL CONTROL, AUDIT FAILURES INFLUENCE AUDITING PRACTICES? - Tariq Tawfeeq Yousif Alabdullah (Transpublika Publisher, 2023)
The main objective of this research is to examine the association between sustainability assurance audit failures and internal control and auditing practices. The study utilizes a quantitative method through a survey of 24 auditors from the State Audit Institution in Oman. The present study tested the hypotheses using Smart-PLS for data analysis. The results revealed that sustainability assurance and internal control have a positive and significant effect on auditing practices, while the factor of audit failures had an insignificant relationship with auditing practice. The present work contributes to practitioners and scholars in the field of auditing techniques by providing implications. It does so by offering empirical evidence to academics, decision-makers, and other interested parties.